Condição bucal precária e seu impacto na qualidade de vida - Santos, Lília Paula de Souza (2016)
Oral health problems are increasingly receiving recognition as important factors that impact quality of life. Socio-dental survey instruments can be used to evaluate this impact, and along with clinical evaluations, are important sources of knowledge for the planning and implementation of health policies that allow the intervention positively. OBJECTIVE: Evaluate the association between oral clinical condition and the perception of its impact on quality of life, taking into account the physical, psychological and social dimensions related to quality of life of individuals attended to in the public health units of Feira de Santana - BA. METHODS: Cross-sectional study developed with adult individuals attended in Family Health Units and the Center for Diabetic and Hypertensive care in the municipality of Feira de Santana--BA. The data were collected through the interviews with application of a questionaire with issues about socioeconomic, demographic, lifestyle, general and oral health condition characteristics, conducting a full oral clinical examination and application of OHIP-14. The statistical analysis included descriptive evaluation of the variables of interest and comparing the total OHIP scores according to the variables of oral health. Association measurements, prevalence ratio (PR) and 95% confidence interval (95% CI), between the occurrence of periodontitis and / or presence of dental caries and the impact on quality of life were obtained by poisson regression with robust variance. RESULTS: they were presented as two scientific articles. In the first article, the findings showed statistically significant associations between dental caries (PRadjusted: 1.43; 95% CI: 1.02-2.01) and severe periodontitis (PRadjusted: 1.72; 95% CI: 1.00-2.98) with the impact of oral health on quality of life. In the second article, it was observed the association between the presence of dental caries combined with periodontitis and the impact of quality of life in oral health (PRadjusted: 1.63; 95% CI: 1.03-2.59). CONCLUSIONS: The findings of this study showed that precarious oral health and accumulation of dental needs (dental caries and periodontitis combined) are associated with self-perceived oral health according the oral health impact profile (OHIP).